Relationship Between Critical Reading Comprehension And Writing Skills - Yanti, Eka Christi (UKMC International Conference (UKMC IC) Proceedings, 2024)
The relationship between critical reading comprehension and writing skills is an important area of study in language education, reflecting the interconnectedness of these two fundamental literacy skills. This study investigates how critical reading, which involves analyzing, evaluating, and synthesizing information from texts, influences and improves writing skills. Critical reading comprehension fosters the development of higher-order thinking skills, which are essential for effective writing. Through a review of the literature and empirical studies, this study highlights that students who engage in critical reading activities show significant improvements in their writing, particularly in areas such as argumentation, coherence, and use of evidence. In this study, the authors used English Language Education students as subjects. The technique used in this study was to conduct a test, namely the first test of twenty reading questions and the second test of writing a descriptive essay. The findings suggest that integrating critical reading exercises into writing instruction can produce a more in-depth and sophisticated writing style. Educational implications include recommendations for curricula to incorporate critical reading strategies to improve writing proficiency. By fostering a symbiotic relationship between these skills, educators can better prepare students for the challenges of academic and real-world communication.